A reference model of j-fakih: learning game to read jawi script via mobile devices for person with disabilities (pwds) - Hussain, Azham; Zainol, Azida; Yasin, Azman
Learning Jawi among deaf people is very challenging if they are not taught using appropriate technique. At the same time, studies have shown that game-based learning is one way of attracting children’s attention in learning Jawi. On the other hand, Fakih has been proven as a learning method for deaf children to read Quran. Accordingly, this study believes that it is also possible to be used in learning Jawi among deaf children. Fakih is a method that uses number and colors to recognize the Arabic characters and also the script. This study proposed a new method for learning Jawi to deaf children by adding hand signs and named as jFakih. Additionally, this study also designs a reference model for jFakih for future development of mobile application. By using waterfall-agile hybrid method, this study gathered the requirements and designed the model using UML technique. The model was verified through prototype development and usability study was carried out to get feedbacks from users. This model is expected to assist and accelerate the process of mobile application development related to fakih method.